RESEARCH OF BOOK MATTER IN LATVIA IN 1918–1944: AUTHORS, TOPICS, PUBLICATIONS, PRESS - ZANDERS, VIESTURS (Knygotyra, 2015)
The research of book matter in Latvia started at the end of 18th century with an essay about the printing houses in Riga written by pastor and bibliophile L. Bergmann. Some important publishing houses got coverage in the publications by A. Bucholtz and A. Poelchau at the end of the 19th – beginning of the 20th centuries. Although the founding of Latvian statehood in 1918 made a definetely new situation for book publishing per se, it didn’t bring substantial changes for research of book matter. Unlike several other humanitarian sciences, research of book matter didn’t receive financial support by state and didn’t get some institutional form as well. The research of book matter had stripes of spontaneous and fragmentary activity. The research was done not only by specialists (publishers, specialists in printing and bibliographers), but by scientists of other fields (historians, linguists, specialists in literature) too. Some fresh ideas about the Livonian book culture during the Middle Ages and Reformation were brought in by the workings of the Baltic historian of German origin, L. Arbusow. The publications of bibliophile J. Misiņš and art historian V. Pengerots told about history of printing enterprises in Latvia. The survey concerning the development of book matters in Latvia written by V. Pengerots was published in “Gutenberg-Jahrbuch” (1935). The periodical “Latvju Grāmata” (“Latvian Book”, 1922–1931) provided diverse information about the current topics in Latvian and foreign book matters though few specific research publications. Due to limited readership the world economic crisis at the beginning of 30ies was fatal for periodical “Latvijas Grāmatrūpniecības Apskats” (“The Review of Latvian Book Industry”, 1928–1931). “Bibliotekārs” (“Librarian”, 1937–1940) published by Latvian Society of Librarians was noticeable for article written by its editor, bibliophile G. Šaurums about ancient prints in Latvian found in foreign libraries. More than 30 publications covering different topics on book matter (including about books in Latvian in the 16th–18th centuries, educational literature) one can find in “Izglītības Ministrijas Mēnešraksts” (“The Monthly of Ministry of Education”, 1920–1939). One should note that the factual information gathered during 20ies and 30ies was later used for monographies about Latvian book matters, published in 60ties and 70ies. During the period the first popular – scientific study in Latvian covering the book matter (“The Book, its history…” by K. Dziļleja, 1935) was published as well. Publications featuring the exhibitions of Latvian books in Moscow (1940) and Leipzig (1942) are distinguished by their representation purposes. During the Nazi occupation articles covering book matter topics were published in periodicals “Izglītības Mēnešraksts” (“Educational Monthly”, 1942–1944) and “Latvju Grāmatnieks” (“Latvian bibliophile”, 1943–1944). The disruption of Latvian independence broke down for a long time an adequate development of Latvian research of book matter. Some authors (K. Draviņš) pursued their scientific work in exile. The others (J. Straubergs, K. Egle) had no access to full-bodied scientific work as the Soviets denied their professional activities in universities and libraries.